Social capital and CO2 emission—output relations: a panel analysis - Ibrahim, Mansor H.; Law, Siong Hook (Elsevier, 2014)
The present paper examines the mitigating effect of social capital on the environmental Kuznets curve (EKC) for CO2 emissions using a panel data of 69 developed and developing countries. Adopting generalised method of moments (GMM) estimators, the paper finds evidence substantiating the presence of EKC. Moreover, the evidence suggests that the pollution costs of economic development tend to be lower in countries with higher social capital reservoir. Surprisingly, there is also evidence to indicate that the income threshold point beyond which CO2 emissions decline is higher in countries with higher social capital. These results are robust to addition of alternative controlled variables in the EKC specification. Thus, in addition to policy focus on investments in environmentally friendly technology and on the use of renewable energy, investments in social capital can also mitigate the pollution effects of economic progress.